An Analysis of Teachers’ Professionality Competences in Teaching English at SMK Negeri 1 Gunungsitoli Alo’oa in 2023/2024 - Teti Mawati Gulo; Riswan Zega; Trisman Harefa; Yasminar Amaerita Telaumbanua (Universitas Muhammadiyah Enrekang, 2024)
Teachers' professional competence is very important to be owned by an educator so that students' abilities can be improved properly. This study aims to find out how the professional competence of teachers and what factors influence the low achievement of teacher professional competence at SMK Negeri 1 Gunungsitoli Alo'oa, especially for two English teachers who became participants in this study. The method used in this research is qualitative method. To obtain the data, the researcher used two data collection techniques, namely observation and interview. After obtaining the data, the researcher analysed the data by using Saputri's theory in Huberman (2023: 30), namely reducing data, displaying data and concluding data. The results of the research are as follows. Of the five indicators of teacher professional competence, two indicators have been achieved, namely indicators of mastery of learning materials and mastery of competency standards, while indicators that have not been achieved are creative development of learning materials, creative development of learning media and utilisation of information technology. The factors that influence the non-achievement of the three professional competencies of teachers are The first factor is the beliefs and values that exist in the teacher. Both teachers do not have the confidence to create new creativity and innovation due to inadequate school facilities. The second factor is personality characteristics, the lack of cohesiveness between teachers in collaborating to improve teachers' professional competence. The third factor is motivation, both teachers are motivated in creating new innovations, the obstacle is the lack of support for these innovations, for example when looking for new innovations there are obstacles in references due to unsupportive internet access. then the fourth factor is emotional problems. Both teachers admitted that they were afraid of making mistakes in creativity because it would hurt if the results of the creativity they created were not used.Based on these results, it can be concluded that the professional competence of teachers in both English teachers at SMK Negeri 1 Gunungsitoli Alo'oa has not been achieved.